Laparoscopic extraperitoneal uterine suspension with suture line instead of mesh. (August 2017) - Liang, J; Chen, G; Deng, L; Liu, FJ; Wu, LJ; Li, Q; Shen, X; Yang, YJ; Ling, B
Abstract : Objective: To compare the safety and effectiveness of two different materials (mesh and suture line) used in laparoscopic extraperitoneal uterine suspension. Design: A retrospective observational study. Setting: Gynaecology departments in two hospitals in China. Population: Women with symptomatic pelvic organ prolapse (POP) of stage II or higher. Methods: The women were divided into two groups according to the two different materials for laparoscopic extraperitoneal uterine suspension: mesh or suture line. The baseline characteristics, perioperative details, complications, objective and subjective indexes of the two groups were compared. Main outcome measures: The primary outcome was subjective satisfaction rate based upon validated questionnaires. The secondary outcome was objective anatomic assessment with the POP‐Q system. Results: No difference was found in baseline characteristics and perioperative details except that there were more cases of cardiovascular disease (CVD) and associated other surgeries in the Line than the Mesh group (36 versus 19, P  < 0.05; 12 versus 2, P  < 0.05). Statistically significant improvements were found in anatomical measures of points Aa, Ba, Ap, Bp, C and TVL ( P  < 0.01), as well as functional and quality‐of‐life measures ( P  < 0.01 for PFDI‐20 and PFIQ‐7) between both groups. The postoperative PFDI‐20, PFIQ‐7 and PGI‐I scores were not different between two groups ( P  > 0.05). Two cases of deep wound infection were observed in Mesh group at 3‐month follow up. Conclusions: Laparoscopic extraperitoneal linear uterine suspension is easy to perform and is associated with fewer mesh‐related complications. It is more secure, especially in elderly women and in those with physical complications. Tweetable abstract: Laparoscopic extraperitoneal linear uterine suspension is safe, with fewer mesh‐related complications. Tweetable abstract: Laparoscopic extraperitoneal linear uterine suspension is safe, with fewer mesh‐related complications.